2010
DOI: 10.1016/j.applthermaleng.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Heat recovery from Diesel engines: A thermodynamic comparison between Kalina and ORC cycles

Abstract: To cite this version:Paola Bombarda, Costante Invernizzi, Claudio Pietra. Heat recovery from Diesel engines: a thermodynamic comparison between Kalina and ORC cycles. Applied Thermal Engineering, Elsevier, 2009, 30 (2-3) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
116
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(127 citation statements)
references
References 20 publications
1
116
0
4
Order By: Relevance
“…Many researchers have studied Kalina Cycle and Rankine Cycle with unconventional working fluids. There are several disadvantages for Kalina Cycle, such as low cycle performance, needing large heat transfer area, needing properties of enduring high pressure and corrosion resistance [3]. ORC is attracting more and more interests in power generation field with low temperature energy.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied Kalina Cycle and Rankine Cycle with unconventional working fluids. There are several disadvantages for Kalina Cycle, such as low cycle performance, needing large heat transfer area, needing properties of enduring high pressure and corrosion resistance [3]. ORC is attracting more and more interests in power generation field with low temperature energy.…”
Section: Introductionmentioning
confidence: 99%
“…Being a mixture, the working fluid evaporates and condensates nonisothermally and this potentially provide the advantage of a better match between non-isothermal heat sources and sinks [3]. The Kalina cycle has been proposed in many different configurations and in the present study, the model is made with a configuration similar to those found in work by Jonsson et al [18] and Bombarda [5], which have been found suitable for marine application. Figure 2 illustrates the process flow diagram of the Kalina cycle and the TC.…”
Section: Kalina Cyclementioning
confidence: 98%
“…The Kalina cycle has in the literature [3,4] been claimed to possess potential to achieve higher conversion efficiencies for WHR in general, compared to both ORC and steam Rankine cycles. Controversy exists however, and modelling efforts [5] have showed that the performance of ORC and Kalina may, at best, may be similar for marine application. For this reason it is the goal of the present study to compare the three mentioned power cycles for the previously mentioned case study.…”
Section: Introductionmentioning
confidence: 99%
“…Bombarda et al [16] carried out a comparative analysis on thermodynamic performance of Kalina and organic Rankine cycles. Ganesh and Srinivas [17] investigated a lowtemperature Kalina cycle to optimize the heat recovery from solar collectors.…”
Section: Introductionmentioning
confidence: 99%